Development of a socially assistive human-robot interface for cardiac rehabilitation - Casas Bocanegra, Jonathan Alejandro (Escuela Colombiana de Ingeniería Julio Garavito, 2019)
According to the world health organization, cardiovascular diseases (CVD’s) are a major cause of death worldwide, taking the lives of 17.9 million people every year. Cardiac Rehabilitation (CR) programs are dedicated to approaching this problem and reduce mortality due to the presence of a second event. However, the main problem regarding these programs is associated with low adherence and attendance to the therapies, causing a major public health issue that generates high health care expenditures. In this context, different approaches have been considered to motivate people to attend the therapies and continue with the treatment. Socially Assistive Robotics (SAR) has been gaining significant attention in multiple health care applications by providing assistance through social interaction rather than physical interaction. Social robots have provided support, motivation, and monitoring in areas such as stroke rehabilitation, patients with dementia, physical rehabilitation, and autism. These interventions have reported promising results, showing that patients feel more engaged and motivated to continue the therapeutic treatments. These findings are encouraging to explore the effect of SAR in CR. This master thesis presents the development and validation of a socially assistive human-robot interface for CR. This interface integrates a Human-Computer interface (HCi) designed to perceive the environment and allow the interaction with the user and the therapy context. In conjunction with the HCi, the system integrates a social robotic platform, which is programmed to socially interact with the user, providing monitoring and motivation, according to the information generated by the HCi. In order to evaluate the effect that the SAR system produces in CR patients, this thesis conducted a series of experimental studies. First, a longitudinal study was carried out with a group of six patients divided into 2 groups (control and intervention) aiming to compare the effect of the robot-therapy against conventional therapy. Furthermore, an acceptance and perception study was conducted for a group of 28 patients and 15 clinicians to evaluate their opinions, experience, and expectations with the system. Results demonstrate significant potential in the incorporation of social robotic companions in CR, where patients that interacted with the robot showed improvement of their physiological condition (i.e., reduction of resting hearth rate and increasing of the recovery capability after exercise) compared to the baseline. Moreover, patients that interacted with the robot felt motivated and encouraged to continue the treatment, and clinicians perceive the system as a useful tool to support their tasks and provide better assistance. Demonstrating that SAR holds promising potential to be a feasible approach that enhances CR effects and help to improve the quality of life of cardiac patients.

Según la organización mundial de la salud, las enfermedades cardiovasculares (ECV) son una de las principales causas de muerte en todo el mundo, cobrando la vida de 17,9 millones de personas cada año. Los programas de rehabilitación cardíaca (CR) están dedicados a abordar este problema y reducir la mortalidad debido a la presencia de un segundo evento. Sin embargo, el principal problema con respecto a estos programas está asociado con una baja adherencia y asistencia a las terapias, lo que causa un problema importante de salud pública que genera altos gastos de atención médica. En este contexto, se han considerado diferentes enfoques para motivar a las personas a asistir a las terapias y continuar con el tratamiento. La robótica de asistencia social (SAR, por sus siglas en inglés) ha recibido una atención significativa en múltiples aplicaciones de atención médica al proporcionar asistencia mediante la interacción social en lugar de la interacción física. Los robots sociales han brindado apoyo, motivación y monitoreo en áreas como la rehabilitación del accidente cerebrovascular, pacientes con demencia, rehabilitación física y autismo. Estas intervenciones han reportado resultados prometedores, mostrando que los pacientes se sienten más comprometidos y motivados para continuar los tratamientos terapéuticos. Estos hallazgos son alentadores para explorar el efecto de SAR en CR. Esta tesis de maestría presenta el desarrollo y la validación de una interfaz humano-robot de asistencia social para CR. Esta interfaz integra una interfaz humano-computadora (HCi) diseñada para percibir el entorno y permitir la interacción con el usuario y el contexto de la terapia. En conjunción con el HCi, el sistema integra Una plataforma robótica social, que está programada para interactuar socialmente con el usuario, proporcionando monitoreo y motivación, de acuerdo con la información generada por el HCi. Para evaluar el efecto que produce el sistema SAR en pacientes con RC, esta tesis realizó una serie de estudios experimentales. Primero, un estudio longitudinal fue llevado a cabo con un grupo de seis pacientes divididos en 2 grupos (control e intervención) con el objetivo de comparar el efecto de la robototerapia con la terapia convencional. Además, se realizó un estudio de aceptación y percepción para un grupo de 28 pacientes y 15 médicos para evaluar sus opiniones, experiencia y expectativas con el sistema. Los resultados demuestran un potencial significativo en la incorporación de compañeros robóticos sociales en RC, donde los pacientes que interactuaron con el robot mostraron una mejora de su condición fisiológica (es decir, reducción de la frecuencia cardíaca en reposo y aumento de la capacidad de recuperación después del ejercicio) en comparación con la línea de base. Además, los pacientes que interactuaron con el robot se sintieron motivados y alentados a continuar el tratamiento, y los médicos perciben la sistema como una herramienta útil para apoyar sus tareas y proporcionar una mejor asistencia. Demostrando que SAR tiene un potencial prometedor para ser un enfoque factible que mejore los efectos de RC y ayude a mejorar la calidad de vida de los pacientes cardíacos.
Desarrollo de una interfaz Humano-Robot basada en robótica social de asistencia para rehabilitación cardíaca
Keywords: Robotica Social; Robot-Humano-Interacción; Rehabilitación Cardiaca; Social Robotics; Human-Robot Interaction; Cardiac Rehabilitation